PKM PENERAPAN MAXIMUM POWER POINT TRACKER (MPPT) PADA SISTEM POMPA AIR SOLAR PHOTO VOLTAIC (SPV) UNTUK RW8 KELURAHAN ROWOSARI KOTA SEMARANG - Titik NURHARYATI1; Bambang SUDARMANTO; Agus MARGIANTONO (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2020)
Rowosari Urban Village is a village located in Tembalang District, Semarang City. The Rowosari Urban Village has an area of ​​719,577 Ha at an altitude of 47 m above sea level with an average rainfall of 2,000 mm / year, an average temperature of 300C. According to Purwoko, SH, Head of Rowosari Village, when met by the Community Partnership Program Team (PKM) in the Rowosari Kelurahan office, problems in Rowosari Kelurahan, especially in RW 8, one of which was the high electricity bill, especially for public facilities such as prayer rooms and low human resources (HR) ), therefore the purpose of this PKM is to reduce electricity bills and increase the human resources of the Rowosari Kelurahan, Tembalang District, Semarang City through training in the Implementation of the Maximum Power Point Tracker (MPPT) in the Water Pump System. To overcome the problems of partners especially the priority that must be addressed, the University of Semarang PKM team used a method with 3 stages of activities namely HR Enhancement through Solar Photo Voltaic (SPV) assembly training, Assistance in Solar Photo Voltaic (SPV) assembly, and Installation of electric pumps that produced from Solar Photo Voltaic (SPV). The results of this PKM activity are water pumps in wells in the RT.02 / RW mosque. 8 Kelurahan Rowosari has used a Solar Photo Voltaic Water Pump (SPV).